Pengaruh Pendekatan SAVI (Somatis, Audiotori, Visual, Intelektual) terhadap Kemampuan Komunikasi Matematika Siswa Kelas VII MTs. Putra Narmada Tahun Pelajaran 2016/2017 - Zainuddin, Toni; Nissa, Ita Chairun; Agusfianuddin, Agusfianuddin (Universitas Pendidikan Mandalika (UNDIKMA), 2017)
Habits of teachers in only use conventional teaching methods in teaching and learning mathematics cause less enthusiastic students to follow the lessons. Therefore, teachers are required to select a model appropriate learning characteristics of students and the material being taught. Thus, students will more easily understand the material. This study aims to determine the effect ofapproach SAVI (Somatic, Visual, Intelectual) the on communication skills of mathematics students of class VII MTs. NW Men 2016/2017 school year. population in this study consisted of 327 students and is where the study sample consisted of two classes of class VII B (experiment) and VII C (control). Determination of the experimental class and control class is determined by Probability Sampling and obtained class VII B as an experimental class while the class VII C as the control class. The results showed the average value of 61.56 while the value - average for the control class 45.17. While Test-T to the achievement of the control class experiment belajarkelas obtained tcount > ttable (3.285> 2.002) that concluded the application of the model approach SAVI (Somatic, Auditory, Visual, Intellectual) affect the ability of students' mathematical communication VII MTs. NW Men Narmada in the academic year 2016/2017.